Obesity, Inflammation and Neurological Alterations. (September 2014) - Spinas, E.; Saggini, A.; Kritas, S.K.; Cerulli, G.; Caraffa, A.; Antinolfi, P.; Pantalone, A.; Frydas, A.; Tei, M.; Speziali, A.; Saggini, R.; Conti, P.
Inflammation, neurodegeneration, imbalance of neurotransmitter systems, oxidative stress and depression are all risk factors for obesity. There is evidence regarding the cross-talk between adipose tissue and the immune system and obese patients may show an alteration of immune functions with major depression, including immune suppression with reduced T-cell and macrophage activity. Obesity is mediated by inflammatory cells such as lymphocytes, macrophages and mast cells which release pro-inflammatory cytokines and chemokines. Obesity-induced leukocyte infiltrations in adipose tissue cause cytokine/chemokine release and inflammation. Here, we report the relationship between obesity, neurological alterations and inflammation.